Yowis Ben’s Agency Changing Structure of Hegemonic Language in Indonesia Cinemas Becomes a Critique of Jakarta’s Culture Industry - Akbar, Moh. Rifaldi (Jurnal Ilmu Komunikasi, 2022)
This study describes cinema production by the Jakarta cultural industry that engages in anti-diversity practices. Cinema production in Jakarta is an industry that standardizes language in the social formation of Indonesian society, which has a variety of vernacular languages. This study aims to evaluate the centralization of the Jakarta Cultural Industry, especially the language practice in film. This study uses the desk research method with data collection techniques in the form of literature studies and digital observations. This research takes the case of Yowis Ben's agency social practice, which has carried out language structuring in the film industry in Indonesia. This study finds that Indonesian is a structure that alienates local languages in the industry and communication style that Jakarta dominates. Jakarta uses Indonesian in its cinematic style of speech as a form of standardization that Jakarta production houses do for for-profit purposes. This research is novel because it discusses the Indonesian language as the hegemony of the cultural industry centralization in Jakarta, which also explains the oppression of ethnic languages in Indonesia in terms of structure and agency theory.